Current International Initiatives in Antiphospholipid Antibody Testing - Willis, Rohan; Harris, E. Nigel; Pierangeli, Silvia S. (Seminars in Thrombosis and Hemostasis, 2012)
Positive results in the anticardiolipin antibody (aCL), anti-β2-glycoprotein I antibody (aβ2GPI), and/or lupus anticoagulant (LA) assays constitute the laboratory criteria for the definite diagnosis of the antiphospholipid syndrome (APS). These tests became available from as early as the1980s, and since then several novel assays have become available that have varied usefulness in the diagnosis and prognosis of APS patients. For almost three decades there has been an ongoing effort to standardize the aCL, aβ2GPI, and LA assays, but there are still reports of significant intra- and interlaboratory variation in the results of all three assays. There have also been numerous issues with the implementation of novel (noncriteria) antiphospholipid antibody (aPL) tests in standard testing panels, due to either lack of standardized testing methods or limited evidence of their clinical utility in APS patients. At the recent 13th International Congress on Antiphospholipid Antibodies (APLA 2010, 13–16 April 2010, Galveston, TX), two task forces were set up to address these problems. This review gives a general description of current problems hindering the standardization of aPL tests and the implementation of novel assays as standard components of aPL testing panels. It also highlights the approach used by APLA 2010 Task Forces to address these problems and presents their recommendations.
Keywords: anticardiolipin antibodies; antiphospholipid antibodies; anti-β2-glycoprotein I antibodies; lupus anticoagulant; standardization